Design and fabrication of an indigenous confined bubble column: Investigation of single bubble ascent - Sikandar Almani; Muhammad Raheel Bawani; Ubedullah Ansari; Masroor Abro; Mashad Hussain; Ali Abbas (Mehran University Research Journal of Engineering and Technology)
In Chemical Process Industries (CPIs) like petrochemicals, biochemicals, and pharmaceuticals, gas-liquid interactions are crucial. Bubble columns are preferred for their low maintenance, absence of moving parts, and efficient mass transfer and mixing. Liquid phases in such systems often shift from Newtonian to non-Newtonian behavior, as seen in materials like molasses, cooking oil, and microalgae, affecting hydrodynamic parameters like gas holdup, mixing time and mass transfer. This study investigated single-bubble dynamics using an Indigenous confined bubble column (6 × 240 × 1140 mm³) in water (Newtonian) and CarboxyMethyl Cellulose (CMC) solutions (non-Newtonian) at 1 g/L, 2 g/L, and 3 g/L. The shadowgraphy technique measured bubble size, terminal velocity, Reynolds number, bubble count, and trajectory. In water, bubbles measured 1.48 mm, with sizes increasing to 1.87 mm and 2.08 mm in 2 g/L and 3 g/L CMC due to higher viscosity delaying detachment. Terminal velocity was 0.22 m/s in water, dropping to 0.11 m/s, 0.107 m/s, and 0.088 m/s in 1 g/L, 2 g/L, and 3 g/L CMC, respectively. Reynolds numbers declined sharply from 335.2 in water to 31.5, 7.9, and 3.5 in CMC solutions, reflecting viscosity's inverse effect. Bubble count increased from 7 per frame in water to 14, 15, and 17 in CMC solutions, as lower terminal velocity prolonged bubble presence. Trajectories were zigzag in water but remained rectilinear in CMC solutions across all concentrations. These findings highlight rheology's significant impact on bubble behavior, which will be essential for optimising process parameters in various CPIs.